Contributor and Victim - Indonesiaâs Role in Global Climate Change with Special Reference to Kalimantan - Prinz, Dieter (Teknik Lingkungan Universitas Islam Indonesia, 2009)
Through rapid deforestation, forest fires, degrading peatlands, and diminishing carbon âsinksâ Indonesiais one of the main contributors to the phenomenon of Global Climate Change. On the other hand,Indonesia will also be a major victim of Climate Change. The combination of high population density onsome islands and high levels of biodiversity, together with 80,000 kilometres of coastline and 17,500islands, makes Indonesia one of the most vulnerable countries to the impacts of Climate Change. Expertsexpect a warming from 0.2 to 0.3Â°C per decade in Indonesia during this century, together with anincrease in annual precipitation across the majority of the Indonesian islands. Additionally there will bea change in the seasonality of precipitation; Borneo may become 10 to 30% wetter by the 2080âs duringDecember-February. As rainfall decreases during critical times of the year this translates into higherdrought risk, consequently a decrease in crop yields, economic instability and drastically moreundernourished people. On the other hand, increased rainfall during already wet times of the year willlead to high flood risk. Rising sea levels and many more extreme weather events will contribute to themany problems caused by Global Climate Change. Indonesia, and Kalimantan in the first instance, hasto take up the challenge of climate change in taking actions at all levels to reduce greenhouse gasemissions, including promoting sustainable use of land and water resources, and putting adaptation intothe development agenda.